Pengembangan Bahan Ajar Menulis Puisi Rakyat Berbantuan Media Gambar “Canva” Untuk Siswa Kelas Vii - Suci Cyntia Sablina Beuty Sakti Situmorang; Khairil Ansari (Universitas Palangka Raya, 2024)
This research aims to develop teaching materials for writing Pantun (a traditional Malay poetry form) using